Analisis Rasio Keuangan dalam Menilai Kinerja Keuangan di Grand Pacific Hotel Bandung - Sri Rizki Asti Karini, Rieke; Apriliyanto, Elton (Manajemen dan Pariwisata, 2024)
This research aims to find out how the financial performance of the Grand Pacific Hotel is for the 2019–2022 period by analyzing the Hotel Financial Report which describes the financial performance that has been achieved through information on the financial position of the Grand Pacific Hotel. . Using quantitative descriptive methods and data in the form of Financial Reports, consisting of the Profit and Loss Report and Balance Sheet of Grand Pacific Hotel. Testing was carried out based on four categories of financial ratios, namely Liquidity Ratios, Solvency Ratios, Activity Ratios and Profitability Ratios. Based on the research results, it was concluded that the Liquidity Ratio, Solvency Ratio, Activity Ratio and Profitability Ratio of Grand Pacific Hotel for the 2019 - 2022 period regarding the company's financial performance were in good condition.